Natalia Milanesio, Destape: Sex, Democracy, and Freedom in Postdictatorial Argentina - Mercader, Sofía (Prismas - Revista de historia intelectual, 2021)
Natalia Milanesio, Destape: Sex, Democracy, and Freedom in Postdictatorial Argentina, Pittsburgh, Pa., University of Pittsburgh Press, 2019, 326 páginas